The boy who lost his face - Sachar Louis 1954-; Louis Sachar (New York : Yearling Book, 2000)
David receives a curse from an elderly woman he has helped his schoolmates attack, and he learns to regret his weakness in pandering to others for the sake of popularity before new friends and a very nice girl help him to be a stronger, more assertive person.
M
b
b